2010
DOI: 10.2165/11533330-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adherence to Interferons in the Treatment of Multiple Sclerosis

Abstract: The findings of low patient adherence and the impact of adherence on relapses and healthcare resource utilization strongly suggest opportunities to reduce healthcare resource utilization and healthcare costs among RRMS patients taking interferon-beta therapy. Efforts should be undertaken to understand and improve medication-taking behaviour in this population so as to minimize the negative impacts of RRMS on patients while reducing unnecessary direct and indirect costs to treat disease exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
212
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(231 citation statements)
references
References 43 publications
7
212
1
11
Order By: Relevance
“…However, switches can also be beneficial to patients, particularly if they have switched due to experiencing breakthrough disease on injectable therapies to a more efficacious therapy. A switch to a more efficacious therapy may promote adherence, which has been shown to be associated with improved clinical outcomes 19 , reduced healthcare resource utilization 22 , reduced incidence of MS-related hospitalization 19 , and improved health-related quality-of-life 24,25 . Tan et al 19 found that patients who were adherent (measured as an MPR of 0.80) had significantly lower odds of relapse than non-adherent patients (odds ratio ¼ 0.71; 95% CI ¼ 0.59-0.85).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, switches can also be beneficial to patients, particularly if they have switched due to experiencing breakthrough disease on injectable therapies to a more efficacious therapy. A switch to a more efficacious therapy may promote adherence, which has been shown to be associated with improved clinical outcomes 19 , reduced healthcare resource utilization 22 , reduced incidence of MS-related hospitalization 19 , and improved health-related quality-of-life 24,25 . Tan et al 19 found that patients who were adherent (measured as an MPR of 0.80) had significantly lower odds of relapse than non-adherent patients (odds ratio ¼ 0.71; 95% CI ¼ 0.59-0.85).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adherence to, and persistence with, DMTs are associated with a reduced risk of relapse 22,23 , reduced healthcare resource utilization 22 , reduced incidence of MS-related hospitalization 19 , and improved health-related quality-of-life 24,25 in patients with MS. First-line injectable DMTs are associated with sub-optimal rates of adherence and persistence 20,22,[26][27][28][29] , and treatment-related issues, such as unresponsiveness and intolerance to GA or IFNs, prompt patients to discontinue or switch therapy 30,31 . A review of DMT discontinuation rates across several countries found that 16-27% of patients discontinued GA or IFN therapy prematurely within 24 months of follow-up, increasing to 43% for GA and up to 34% for IFNs when patients were followed for longer than 24 months 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients that were adherent over the entire study period had a 3% lower risk of relapse (P < 0.05) over the 3-year study period. 2 Physicians and pharmacists who care for patients using specialty products strive to improve adherence in an effort to improve outcomes and lower morbidity and its associated costs. In a comparison of immunosuppressive specialty products, patients receiving services and specialty medication from specialty pharmacies had improved adherence rates (87% vs. 83%) compared with patients receiving the same medications in traditional retail pharmacies.…”
Section: Adherencementioning
confidence: 99%
“…[1][2][3][4] An observational, multicenter, multinational phase 4 study of over 2,000 patients with an average treatment duration of 31 months found that the most common reason for medication nonadherence was forgetting to take the injection (50.2%). 3 Twenty-five percent of the patients in this analysis were nonadherent (i.e., missed at least 1 dose).…”
mentioning
confidence: 99%